PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP FINANCIAL PERFORMANCE MELALUI VARIABEL INTERVENING EMPLOYEE SATISFACTION DAN CUSTOMER SATISFACTION DI PERUSAHAAN PERBANKAN SURABAYA - Vincentius - Rongkang; yulius - yogi (Business Accounting Review, 2016)
This Study aimed to examine the affect of transformational leaadership to financial performance through employee’s satisfaction and customer’s satisfaction as intervening variables in banking corporate Surabaya. The sample used in this study was 30 banking corporate in Surabaya listed in Bursa Efek Indonesia (BEI) with 300 respondents and Return of Asset in 2012 until 2014. Partial Least Square method was used to analys the data. The result of this study showed that transformational leadership had positive and significant affect on employee’s satisfaction, employee satisfaction’s had positive and significant affect on customer’s satisfaction, customer’s satisfaction had positive and significant affect on financial performance, and transformational leadership had positive and significant affect on financial performance